Analysis of the Effect of Adding Insulators to Reservoirs Tank on Heat Losses as a Result of the Heat Exchanger System (Double Tube) for Water Heater - Nailul Atifah; Dian Wiranda Tahami; Astuti, Fifit (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Air Conditioners release heat to the environment through a condenser and contribute to global warming. This can be minimized by utilizing exhaust heat as a source of water heating energy. This study aims to determine the effect of adding insulators to reservoir tanks on the temperature of the water that has been heated. This research was carried out by installing a double tube heat exchanger between the compressor and the condenser to transfer heat from the refrigerant of the air conditioner to the water. The volume of water used is 10 liters and 15 liters and the condition of the reservoir tank is insulated and the tank is uninsulated. The results showed that the water temperature in the reservoir tank fitted with an Armaflex insulator was 63.4oC at a water volume of 10 L and 60.3oC at a water volume of 15 L while the water temperature in a reservoir tank without an insulator was 57.7oC at a water volume of 10 L and 52.3oC at a water volume of 15 L. The heat loss of conduction in the insulated reservoir tank at the 50th minute was 3.94 kJ for a volume of water of 10 L and 3.70 kJ for a volume of water 15 liters, while the heat loss of conduction in a reservoir tank without an insulator is 2,404.46 kJ for a volume of 10 liters of water and 2,129.66 kJ for a volume of 15 liters of water. The use of Armaflex insulators in reservoir tanks results in thermal efficiency of more than 95% for 10 liter and 15 liter water volumes, but as the water temperature increases to the 50th minute, the efficiency decreases but is still above 95%. Meanwhile, the uninsulated reservoir tank provides a much lower thermal efficiency, which is 27.22% and 25.57% for the water volume of 10 liters and 15 liters respectively in the first 5 minutes of air conditioning operation, and continues to decrease to 1.88% and 2.30% in the 50th minute. This shows that the use of Armaflex insulators in reservoir tanks exhibits higher water temperatures, has a very significant effect in reducing heat loss to the environment, and higher thermal efficiency than non-insulated reservoir tanks.